CALLED TO ACTION: DIALOGUE AROUND PRAXIS FOR RECONCILIATION - MacDonald, Jennifer; Markides, Jennifer (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
Education for reconciliation is centered on renewing Indigenous-settler relations. In this article, two graduate students share their experiences as they endeavour to take up a praxis for reconciliation. Positioned by their different cultural identities, they join in a duoethnographic conversation, to reflect on their learning and to share their successes, insights, and tensions as they navigate various complexities. Through their reflective process, they ask: What might collective enactment look like and what forms might it take in education? As they journey together, they discuss the need for spaces that promote vulnerability and openness, and the strength of land-based and grassroots learning opportunities.